The Interpretations of Social Innovation and the Helix Models through a System of University Relations - Zoltán Birkner; Tivadar Máhr; Nora Rodek Berkes (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
According to the triple helix model, the dynamic of the innovation system development of a region or sector is determined by the closeness and intensity of state - company - university collaborations. The fourth spiral assumes the importance of the civil society. The appearance and acceptance of the third and fourth spiral model means the birth of the concept of social innovation and the beginning of its research. The fifth helix, that is the ecological approach, strengthens further the possibility of the interpretation of social innovation as the knowledge-based development, the social, political and civil dimensions can be expanded by the issue of sustainability. In 2015 a research was carried out focusing on the tender and corporate relationships of a major university. It was intended to determine these relationships on the basis of social innovation capabilities and the areas of the helix-s theory were also sought in these interactions. In conclusion, the universities are not only determinative in case of the triple helix model, but they also have an outstanding role in the development of social innovation
Keywords: O3; O35; 330; Helix models; innovation; social innovation; university relations